Co-Parenting Management; Shaping Early Childhood Cultural and Language Adaptation - Abu Hasan Agus R; Akmal Mundiri; Ummi Maghfirah; Fadilatul Munawwaroh (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Problems of communication and interaction between preschoolers, unwittingly have an important role in having a high ability to respect culture and language. Children's development is not only influenced by the quantity of time spent with parents, but parents must pay attention and understand the parenting style used when interacting with children. The purpose of this study was to determine the parenting style of parents in shaping the cultural and language adaptations of early childhood. This study used a qualitative approach with a type of field research. The data collection techniques used were observation guidelines and interviews with the principal, homeroom teacher for classes A1 and B1, and two parents at Ummi Sundari Sidomukti Kindergarten, Kraksaan. The data analysis technique used the Miles and Huberman Interactive Model with data reduction activities, presenting data, and drawing conclusions. The results showed that Co-Parenting management in shaping the adaptation of Ummi Sundari Sidomukti Kindergarten children to culture and language was pursued by 2 educational concepts namely guided by local and national languages and internalization of tolerance. This research demonstrated parenting styles in managing positive values in children's affective and psychomotor aspects.